Perspektif Pendidikan Agama Kristen Contextual Teaching and Learning (CTL) dalam Misi Kontekstual di Era Postmodern - Patikan, Krisnawati; Stefanus, Tonny Andrian (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This article aims to examine Contextual Teaching and Learning (CTL) in the perspective of Christian Religious Education as an approach that supports the implementation of contextual mission in the postmodern era. This study uses a qualitative descriptive method with a literature review approach. Data were obtained from scientific articles, theological journals, and relevant literature discussing CTL, contextual theology, Christian Religious Education, and contextual mission. Data analysis was conducted narratively and interpretatively to examine the concepts, strategies, and implications of CTL in Christian Religious Education learning. The results of the study indicate that CTL is theologically compatible with contextual theology because it places the Christian faith as an incarnational and dialogical faith with the socio-cultural context of students. CTL is also pedagogically relevant because it encourages participatory, reflective, and life-based learning, and missionarily strengthens the role of Christian Religious Education as a means of contextual witness to the Gospel in a pluralistic society.